Influence of PbX2 (X = F, Cl, Br) content and thermal treatment on structure and optical properties of lead borate glasses doped with rare earth ions - Pisarska, Joanna; Lisiecki, Radosław; Dominiak-Dzik, Grażyna; Ryba-Romanowski, Witold; Goryczka, Tomasz; Grobelny, Łukasz; Pisarski, Wojciech A. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Oxyhalide lead borate glasses doped with rare earth ions have been studied before and after thermal treatment. The rare earths as optically active ions were limited to the Er3+ ions. Near-infrared luminescence due to the main 4I13/2–4I15/2 laser transition of Er3+ was registered. The introduction of PbX2 to the borate glass results in a reduction of spectral linewidth and an increase of luminescence lifetime of 4I13/2 state of Er3+ ions. The unusual large spectral linewidth for 4I13/2–4I15/2 transition of Er3+ in the oxide glass host was obtained, whereas the luminescence decay from 4I13/2 state is longer for a sample with PbF2 than PbCl2 and PbBr2. Heat treatment introduces transformation from a glass to transparent glass-ceramic (TGC). The coordination sphere around Er3+ ions is changed, giving important contribution to the luminescence characteristics. The spectroscopic consequence of this transformation is the increase of luminescence lifetime and the narrowing of spectral lines of Er3+.
Optica Applicata, Vol. 40, 2010, nr 2, s. 351-358
Keywords: optyka; lead borate glasses; rare earth ions; thermal treatment; luminescence; up-conversion